Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jnr.24038
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of exogenous acetate and glutamate as astrocyte substrates examined in acute brain slices from female mice using methionine sulfoximine (MSO) to inhibit glutamine synthesis

Abstract: Removal of endogenously released glutamate is mediated primarily by astrocytes and exogenous 13 C-labeled glutamate has been applied to study glutamate metabolism in astrocytes. Likewise, studies have clearly established the relevance of 13 C-labeled acetate as an astrocyte specific metabolic substrate. Recent studies have, however, challenged the arguments used to anchor this astrocyte specificity of acetate and glutamate. The aim of the current study was to evaluate the specificity of acetate and glutamate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…We have previously described similar effects of MSO on metabolism of the well-known astrocytic substrate [1,2- 13 C]acetate [ 43 ], further supporting that astrocytes are the main cellular compartment of C8 and C10 metabolism. Furthermore, we have previously demonstrated that transfer of astrocyte-derived glutamine to neurons is maintained in our slice incubation set-up [ 43 , 60 ], implying that the decreased neuronal GABA synthesis in the presence of MSO is indeed caused by the absent astrocyte glutamine supply. Insufficient astrocyte glutamine synthesis can lead to seizures [ 24 ] and reduced expression of GS has been found in the epileptic hippocampus [ 23 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We have previously described similar effects of MSO on metabolism of the well-known astrocytic substrate [1,2- 13 C]acetate [ 43 ], further supporting that astrocytes are the main cellular compartment of C8 and C10 metabolism. Furthermore, we have previously demonstrated that transfer of astrocyte-derived glutamine to neurons is maintained in our slice incubation set-up [ 43 , 60 ], implying that the decreased neuronal GABA synthesis in the presence of MSO is indeed caused by the absent astrocyte glutamine supply. Insufficient astrocyte glutamine synthesis can lead to seizures [ 24 ] and reduced expression of GS has been found in the epileptic hippocampus [ 23 ].…”
Section: Discussionsupporting
confidence: 53%
“…5 ). The GS inhibitor methionine sulfoximine (MSO) was applied at 5 mM, which we have previously shown is sufficient to effectively inhibit GS activity in brain slices [ 43 ]. As expected, GS inhibition abolished the 13 C accumulation in glutamine from metabolism of [U- 13 C]C8 and [U- 13 C]C10 (C8: 8.7 ± 1.9% of control, C10: 3.7 ± 0.5% of control).…”
Section: Resultsmentioning
confidence: 99%
“…However, this view has been questioned by several studies, indirectly showing a metabolic link between GABA and astrocyte‐derived glutamine. First, glutamine is a precursor for GABA synthesis (Duarte & Gruetter, 2013; Sonnewald et al, 1993) and inhibition of glutamine synthesis depletes the GABA pool (Andersen, McNair, Schousboe, & Waagepetersen, 2017; Fonnum, Johnsen, & Hassel, 1997), and hereby hampers inhibitory transmission (Ortinski et al, 2010). Inversely, cerebral in‐vivo infusion of GABA stimulates glutamine synthesis (Juhasz et al, 1997), whereas inhibition of GABA metabolism depletes the glutamine pool (Paulsen & Fonnum, 1988; Pierard, Peres, Satabin, Guezennec, & Lagarde, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that the db/db mouse exhibits a reduced hippocampal expression of GAD [ 26 ]. Astrocyte-derived glutamine is the main precursor for neuronal GABA synthesis, and the significance of this has been established in our current incubation setup [ 29 ]. The decreased enrichment in GABA M+4 could be explained by an impaired transfer of astrocytic glutamine to neurons.…”
Section: Discussionmentioning
confidence: 99%